A novel germline inactivating mutation in the CASR gene in an Italian kindred affected by familial hypocalciuric hypercalcemia - Falchetti, Alberto; Gozzini, Alessia; Terranegra, Annalisa; Soldati, Laura; Vezzoli, Giuseppe; Leoncini, Gigliola; Giusti, Francesca; Franceschelli, Francesco; Masi, Laura; Tanini, Annalisa; Cavalli, Loredana; Brandi, Maria Luisa (European journal of endocrinology, 2012)
ObjectiveFamilial hypocalciuric hypercalcemia (FHH) syndrome is a rare benign condition, inherited as an autosomal dominant trait, in which inactivating mutations of the calcium-sensing receptor (CASR) gene affects the body's ability to regulate calcium homeostasis. Its outcome is featured by increased levels of serum calcium, moderate hypophosphatemia, and inadequately normal or elevated circulating parathyroid hormone levels. Affected patients are mostly asymptomatic and do not benefit from surgical resection of their mildly enlarged parathyroids.DesignWe evaluated for hypercalcemia an Italian family that was identified via a young adult male proband referred to our center for parathyroidectomy.MethodsThe patients and the family members were evaluated both biochemically and genetically as suspected FHH subjects. An in vitro functional study was performed by site-directed mutagenesis, and CASR activity was monitored by measuring intracellular calcium ([Ca2+]i).ResultsThe patient had a novel germline heterozygous CASR mutation (c.361_364GATT; p.D121del/fsX122). The mutation caused a premature stop codon at codon 122, exiting a truncated protein. The biochemical phenotype of all family members carrying the heterozygous deletion was concordant with classic FHH syndrome.ConclusionsOur findings confirm the role of CASR gene mutational analysis to offer a valuable addition for the recognition of FHH in hypercalcemic patients not yet characterized for a positive familial history of hypercalcemia, the only condition that identifies CASR gene mutations in hypercalcemia.